2014
DOI: 10.1128/jvi.01405-14
|View full text |Cite
|
Sign up to set email alerts
|

Annexin V Incorporated into Influenza Virus Particles Inhibits Gamma Interferon Signaling and Promotes Viral Replication

Abstract: During the budding process, influenza A viruses (IAVs) incorporate multiple host cell membrane proteins. However, for most of them, their significance in viral morphogenesis and infectivity remains unknown. We demonstrate here that the expression of annexin V (A5) is upregulated at the cell surface upon IAV infection and that a substantial proportion of the protein is present in lipid rafts, the site of virus budding. Western blotting and immunogold analysis of highly purified IAV particles showed the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…Rimmelzwaan. Cells were cultured as previously described (Berri et al, 2014). The following reagents were used in the study: monoclonal anti-tubulin antibody (Sigma Aldrich), polyclonal anti-p-ERK antibody (Cell Signaling Technology), anti-viral M2 protein (Santa Cruz), and oseltamivir (Sigma-Aldrich).…”
Section: Rimmelzwaanmentioning
confidence: 99%
“…Rimmelzwaan. Cells were cultured as previously described (Berri et al, 2014). The following reagents were used in the study: monoclonal anti-tubulin antibody (Sigma Aldrich), polyclonal anti-p-ERK antibody (Cell Signaling Technology), anti-viral M2 protein (Santa Cruz), and oseltamivir (Sigma-Aldrich).…”
Section: Rimmelzwaanmentioning
confidence: 99%
“…An exploitation of virus-incorporated AnxA2 to promote the conversion of plasminogen to plasmin on the cell surface was reported to be utilized, at least in a supportive manner, by herpesvirus and IAV [124][125][126][127]. Virus-incorporated AnxA5 assists IAV infection through the inhibition of interferon-mediated host cell protection [128]. Whether the specific binding of anxA5 to a hepatitis B virus (HBV) surface antigen [129,130] mediates a similar function, thereby affecting the host cell susceptibility to HBV [131][132][133][134] remains to be investigated.…”
Section: Annexins and The Host/pathogen Interfacementioning
confidence: 99%
“…Recently, it was found that annexin V is upregulated and translocated to the cell surface upon IAV infection. Localizing to lipid rafts, annexin V gets incorporated into IAV particles and is associated with a decrease in g-interferon signalling in newly infected cells, leading to an increase in viral replication (Berri et al, 2014). Intriguingly, not only annexins but also other host-cell proteins described to be incorporated into IAV have been reported to be incorporated into other enveloped viruses.…”
Section: Incorporation Of Cellular Proteins Into Virionsmentioning
confidence: 99%